Religious moderation of Islamic university students in Indonesia: Reception of religious texts - Afwadzi, Benny (HTS teologiese studies, 2024)
Religious moderation has been popular and widely promoted to students as a countermeasure to radicalism. However, it runs across several challenges. Not to mention that radicalism has extended its influence within Islamic universities in Indonesia. Many research organisations have found that Indonesian students tend to be radical. Hence, the discussion around religious moderation among students highlights its urgency. With emphasis on the reception of Islamic university students to religious texts, this study proposed the appropriate approach to religious moderation in the context of plural Indonesian society with the reception of Qur’anic verses and hadiths that promoted moderation. It employed a qualitative approach with a purposive sampling technique involving 81 students of Islamic Religious Education of UIN Maulana Malik Ibrahim Malang as the research subjects. They were students from four semester IV and VI classes. This study revealed several key findings: firstly, the majority of students equate religious moderation with religious tolerance; secondly, students draw from a range of verses and hadiths that emphasise religious moderation, primarily on tolerance promotion; and thirdly, students’ application of religious moderation based on religious texts manifests through verbal, written and practical approaches. This study presents a model for developing religious moderation rooted in students’ comprehension of religious texts advocating moderation. This study implies using religious texts to promote moderate thought to lessen radicalism and intolerance in the world.Contribution: This study introduces a religious text-oriented approach to enhance the development of religious moderation, thereby refining strategies and methods that have predominantly emphasised aspects of social reality. The religious texts that advocate for moderation are accepted and applied by students in their lives. This contribution is crucial to lessening radicalism and intolerance in Indonesia.